Left Atrial Stiffness Is Increased in Pediatric Hypertrophic Cardiomyopathy and Offers Incremental Value in Predicting Major Adverse Cardiac Events in This Group - Ryusuke Numata; Renzo Calderon‐Anyosa; Sarina Sun; Hunter L. Kauffman; Yan Wang; Tomoyuki Sato; Daisuke Matsubara; Anirban Banerjee (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Determining risk factors by echocardiography to prevent major adverse cardiac events (MACE) is crucial in pediatric patients with hypertrophic cardiomyopathy. Recent studies have shown that left atrial (LA) stiffness may serve as surrogate marker in children, to differentiate elevated pulmonary capillary wedge pressure from normal. Methods We retrospectively enrolled 239 pediatric patients with hypertrophic cardiomyopathy. They were divided into 2 groups: MACE (n=79) and non‐MACE (n=160) groups. Noninvasive LA stiffness was calculated as the ratio of average E/e′ to peak LA strain obtained by 2‐dimensional speckle‐tracking echocardiography. Baseline evaluation was defined as the echocardiogram performed at the time of referral, before the occurrence of a MACE, including appropriate implantable cardioverter‐defibrillator intervention, myomectomy, heart transplant, or cardiac death. Results The MACE group showed significantly decreased left ventricular peak longitudinal strain compared with the non‐MACE group, with no significant difference in left ventricular ejection fraction. Peak LA strain was significantly reduced (22.5±7.1% versus 30.4±7.3%; P<0.001), whereas LA stiffness was significantly increased (median 0.57 [IQR, 0.37–0.91]%−1 versus 0.31 [IQR, 0.22–0.42]%−1; P<0.001) in the MACE group. LA stiffness was the superior‐most index for predicting MACE (C‐index, 0.75; cutoff value, 0.31%−1), and even in cross‐validation, the C‐index consistently demonstrated the highest predictive ability (LA stiffness, 0.746 [95% CI, 0.737–0.753]). Moreover, LA stiffness was independently associated with increased risk of MACE (HR, 1.12 [95% CI, 1.07–1.17]; P<0.001). Conclusions LA stiffness is a newly described index, which may be of incremental value in predicting risk of MACE in pediatric patients with hypertrophic cardiomyopathy.